Clinical systematization of tumor-like formations and tumors of embryonic fissures of the incisal sections of the upper and lower jaws - Shuvalov, Сергій Михайлович; Krynychnykh, Ганна Ігорівна (Actual Dentistry, 2022)
Purpose: to systematize pathological formations of embryonic fissures according to their localization and proliferative activity. Materials and methods. Own observations and literature data were used to create a systematization of tumors and tumors of similar formations in the incisal and globulo-maxillary areas of the upper jaw. Results of the study. In the domestic literature, one of the first systematizations of odontogenic jaw cysts were the classifications of P.P. Lvov, A.A. Limberg, A.A. Kyandsky (1938), A.I. Evdokimov and G.A. , A.A. Kolesova (1964), in which, on the basis of clinical data, two types of cysts were distinguished primarily – radicular and follicular, as well as rare traumatic and cholesteatoma [2, 4, 5, 6, 7, 8, 9]. ore successful was the morphological classification of II Ermolaev (1964), who divided all odontogenic neoplasms into three main groups: epithelial, connective tissue and mixed [2, 6]. However, there are still controversial points in the classification and lack of information regarding non odontogenic cystic formations of the jaws. Findings. Cysts of embryonic fissures are a group of numerous pathologies represented by both odontogenic and non odontogenic formations that require careful differential diagnosis. Treatment of non-odontogenic cysts of embryonic fissures requires the most radical surgical interventions, such as perforation of cystic cavities and deepening of their walls. In order to determine the course of development of tumors and tumor-like lesions, it is necessary to conduct an immunohistochemical study to determine the degree of aggressiveness of these pathologies, followed by their division into high-, medium-, low-proliferative active lesions, which will allow timely detection of malignant changes. The proliferative activity of lesions in the globulo-maxillary area is the most pronounced, which requires active treatment tactics, while this indicator is less in the midline. Pathologies of the median incisive area of the upper jaw are most prone to suppuration.